ҚАРАҚАЛПАҚСТАН ОЙКОНИМЛЕРИНИҢ ЭТНОМӘДЕНИЙ ӨЗГЕШЕЛИКЛЕРИ - Қурбанов, М.Д. (SCIENCE and SOCIETY, 2023)
The article analyzes the ethnocultural and semantic features of the oikonyms of Karakalpakstan. Toponyms reflect the socio-economic life, material and spiritual culture of the local population, the importance of studying this type of oikonyms is explained in detail. There is used toponymic and ethnographic data are used.
Keywords: toponym; oikonym; people; nation culture; material culture; spiritual culture